Human biomonitoring survey (Pb, Cd, As, Cu, Zn, Mo) for urban gardeners exposed to metal contaminated soils. (1st November 2022) - Petit, Jérôme C.J.; Maggi, Patrick; Pirard, Catherine; Charlier, Corinne; Ruttens, Ann; Liénard, Amandine; Colinet, Gilles; Remy, Suzanne
Abstract: Eighty eight adult gardeners and their relatives volunteered to provide urine and blood samples for a human biomonitoring survey among users of one of the biggest allotment garden from Wallonia, showing high trace metal(oid) concentrations in soils. The purpose was to determine if environmental levels of lead (Pb), cadmium (Cd) and arsenic (As) led to concentrations of potential health concern in the study population. Blood and urine biomarkers were compared to reference and intervention cut-off values selected from the literature. The study population exhibited (i) moderately high blood lead levels with median value of 23.1 μg/L, (ii) high urinary concentrations of speciated As (inorganic arsenic and its metabolites) with a median value of 7.17 μg/g.cr., i.e. twice the median values usually observed in general populations, and (iii) very high Cd levels in urine with a median value of 1.23 μg/L, in the range of 95th-97.5th percentiles measured in general adult populations. Biomarker levels in the study population were also mostly above those measured in adults from local populations living on contaminated soils, as reported in the current literature. All biomarkers of Pb, Cd and As showed weak to strong statistically significant correlations, pointing towards a joint environmental source to these three contaminants as being at least partially responsible for the high exposure levels observed. Urine and blood biomarkers show statistically significant associations with variables related to individual characteristics (age, smoking status, …) and Pb domestic sources (Pb pipes, cosmetics, …) but involves also behavioral and consuming habits related to gardening activities on the contaminated allotment garden. At such levels, owing to co-exposure and additive effects of Cd, As and Pb regarding renal toxicity known from literature, the study strongly suggests that this population of gardeners is at risk with respect to chronic kidney diseases. Graphical abstract: Image 1 Highlights: Allotment garden show Pb, Cd and As contaminated soils. Non-compliance to EU regulation 1881/2006 was 30% for local vegetables & fruits. Gardeners show urine Cd and As within 95th percentiles of general populations. High urine Cd and As in gardeners are probably due to intense exposure to soils.